Modeling and forecasting abnormal stock returns using the nonlinear Gray Bernoulli model - Bahar Doryab; Mahdi Salehi (Journal of Economics, Finance and Administrative Science, 2018)
This study aims to use gray models to predict abnormal stock returns. Design/methodology/approach Data are collected from listed companies in the Tehran Stock Exchange during 2005-2015. The analyses portray three models, namely, the gray model, the nonlinear gray Bernoulli model and the Nash nonlinear gray Bernoulli model. Findings Results show that the Nash nonlinear gray Bernoulli model can predict abnormal stock returns that are defined by conditions other than gray models which predict increases, and then after checking regression models, the Bernoulli regression model is defined, which gives higher accuracy and fewer errors than the other two models. Originality/value The stock market is one of the most important markets, which is influenced by several factors. Thus, accurate and reliable techniques are necessary to help investors and consumers find detailed and exact ways to predict the stock market.
Keywords: 330; Abnormal returns; Gray theory; Nash nonlinear gray Bernoulli model; Nonlinear gray Bernoulli model